Qualitative research methods for the social sciences - Lune, Howard (Pearson Education Limited, 2017)
For courses in Research Methods in Political Science and Sociology, and in Qualitative Research Methods Raising questions, rather than giving answers Qualitative Research Methods for the Social Sciences is written with the recognition that different researchers in different fields each bring their own needs and intentions to the process. Authors Howard Lune and Bruce Berg aim to guide the reader through the process of research planning, carrying out one's projects, and making sense of the results. Each chapter provides examples of the best and worst approaches to the kinds of questions that.